Hotel Rebranding: Marketing Plan for Piter Inn Petrozavodsk - Borisova, Kseniia; Razumeiko, Anastasiia (Kajaanin ammattikorkeakoulu, 2018)
This thesis is commissioned by Piter Inn Petrozavodsk, the biggest hotel in Karelia, Russia. The hotel has been a franchise of the Park Inn brand until August of 2017, when the owner had decided to relinquish the franchise and changed the name to Piter Inn Petrozavodsk. Thus, this study aims to provide the company with marketing plan that will help solve the main research problem: how to rebrand the hotel. The research is mainly based on marketing tools, such as marketing mix, PESTEL, SWOT, and Porter’s five forces. Additionally, the study shows the basic fundamentals of strategic management, online marketing, and branding. The analyses for the research are based on quantitative and qualitative methods. The data collection methods are the questionnaire for the guests and face-to-face interviews with the directors of various departments respectively. The results and findings of the thesis are associated with the changes in the company’s operations and marketing actions. The suggested strategies and ideas can be a source of gaining a competitive advantage for the hotel. According to the research outcome, all findings and recommendations should be considered as guidelines and supportive material.